A time-motion analysis of field training in elite soccer during the competitive season - Scott, B.; Taaffe, D. (Journal of Science and Medicine in Sport, 2011)
Time-motion analysis of match performance in elite soccer has been studied extensively in recent years. To date, however, no published research has been conducted to analyse the movement characteristics of complete field training sessions in elite soccer. Purpose: The current study aimed to quantify the movement characteristics of field training for elite soccer during the competitive season. Methods: 15 professional soccer players (age 24.9; range 18-36 yrs; mass 77.6 ± 7.5 kg) encompassing a range of field playing positions were monitored across 23 field training sessions (n=94) during the 2010-2011 Australian A-League season. Players completed training sessions whilst wearing a Minimaxx GPS device (Firmware v6.59; Catapult Innovations, Scoresby, Australia) recording at 5 Hz. The GPS unit was positioned in a pocket located between the scapulae, in an undergarment worn by the player. Session-RPE was recorded using a Category Ratio-10 scale 30 minutes post session to quantify training intensity and internal training load (TL). Results: Session duration ranged from 38.2-117.1 min. Total distance (TD) travelled was 4474.3 ± 1335.6 m, with meterage measuring 61.9 ± 8.9 m·min-1. Players covered 3907.6 ± 1129.0 m in low-intensity running (LIR; <14.4km·h-1). Time spent in LIR was 70.3 ± 16.7 min, equating to 97.4 ± 1.0% of the total training duration. Distance covered and time spent in high-intensity running (HIR; >14.4km·h-1) were 561.9 ± 268.2 m and 1.9 ± 0.9 min, with very high-intensity running (VHIR; >25.2 km·h-1) contributing 143.0 ± 107.1 m and 0.4 ± 0.3 min. Session-RPE recordings ranged from 1-8, (mean = 4.2 ± 1.6), and session-RPE internal TL was 320.4 ± 168.9. Conclusions: It is evident that in-season field training sessions for elite soccer involved extensive periods of LIR and a lower contribution of HIR and VHIR to TD and duration. These findings are likely related to extensive technical and tactical activity and low-intensity in-season training to allow for adequate recovery from frequent match-play. However, it is also possible that due to a strong emphasis on small-sided games and drills in small areas, the distance and duration of HIR bouts may be restricted, resulting in fewer high-velocity efforts. The results of the current study highlight that in-season field training in elite soccer contains a large volume of LIR. Whilst low-intensity post-game recovery is a vital component of in-season training, coaches should ensure a sufficient high-intensity training stimulus so that players maintain the physiological parameters required for elite soccer performance.